Fatores associados ao sono de docentes universitários. - Schattan, Rosângela Bampa (2017)
Introduction: The work demand of college educators can generate great physical and psychological distress, with deleterious health effects, such as sleeping disorder. Objectives: To evaluate the association of social and psychological aspects of work and health with the sleeping characteristics of college educators, as well as correlate the work capacity with fatigue symptoms and minor psychiatric disorders and to compare the duration of sleeping and waking up hours before and after the vacation period. Materials and methods: This is a cross-sectional study of quantitative approach with 123 college educators at a University in Santos-Brazil during 2016 and 2017. Data collection was performed at two different moments: the first part was the application of an on-line instrument containing several validated questionnaires, adapted to the reality of the present investigation. The instrument was divided in three branches: 1. Social-demographic profile and life style; 2. Aspects related to the work; 3. Questions about sleeping conditions and health. The second part consisted of the completion of a diary of sleeping patterns and activities at the end of the academic semester (Phase 1 - before vacations, n=26) and at the beginning of the new one (Phase 2 - after vacations, n=16). For statistical evaluation, hypothesis tests of Pearson's Chi-square or Fisher's exact tests were used. Poisson regression analysis with robust variance, the one way ANOVA with repeated measures and the linear regression analysis were also applied. Results: Individuals average age was 56.3 years (SD 10.4 years), with a majority of the feminine sex (54.5%), living with a partner (74%), had a second job (67.4%), has been working in the institution for an average of 15.3 years (SD 10.4) with an average working hours in the institution of 24.5 hours/week. Most of the college educators showed bad sleeping quality during working days (70.1%), being a little less prevalent on non-working days (49%). College educators with chronic muscle skeletal symptoms showed higher prevalence ratio of bad sleeping quality during working days when compared with those with no symptoms (PR 1.84, CI 95% 1.06-3.20). During non-working days, the prevalence ratio was two times higher (PR 3.13, CI 95% 1.46-6.71). About 1/3 of the college educators showed insomnia symptoms (31.7%). Moreover, having a higher fatigue perception and being sedentary increased the insomnia prevalence ratio when compared to the college educators with lower fatigue perception and physically active (PR 2.66 - CI 95% 1.18-6.01 and PR 2.34 - CI 95% 1.04-5.25, respectively). No differences were observed between averages of sleeping aspects and activities concerning phases 1 and 2. The working capacity was negatively correlated with the fatigue disorders amongst the participants. Conclusion: College educators studied showed high prevalence of insomnia symptoms and bad sleeping quality. Chronic muscle skeletal symptoms, fatigue and sedentary habits negatively interfered in the sleeping patterns of the group. The vacation period did not interfere the sleep aspects evaluated.